DIE VROU IN UNIFORM: STANDPUNTE EN BESKOUINGE - Meyers, E.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
The increasing application of women in uniform is inviting considerable discussion in current literature. The position of the woman in uniform is at present placed under much closer scrutiny, as a result of various factors, such as the rise of feminism, revolutionary social changes, the entrance of women into the different occupational sectors and the principle of the equality of mankind (egalitarianism). A wide spectrum of aspects connected with the position of women in a military situation is analysed, and the divergent points of view maintained by different communities on this subject are taken into account.